ОЦІНКА ПАРАМЕТРІВ І ХАРАКТЕРИСТИК КОРЕКТОРА КОЕФІЦІЄНТА ПОТУЖНОСТІ НА ОСНОВІ ІМПУЛЬСНИХ ТА КВАЗІРЕЗОНАНСНИХ ПЕРЕТВОРЮВАЧІВ ЕЛЕКТРОЕНЕРГІЇ - Денисов, Ю.О.; Городній, О.М.; Гордієнко, В.В.; Вершняк, Л.В.; Димерець, А.В. (Інститут електродинаміки НАН України, Київ, 2018)
Models of pulse converters (PC) with pulse-width modulation (PWM) and zero-current-switch quasi-resonant pulse converter (QRPC-ZCS) with pulse- frequency modulation (PFM), which operate as part of a power factor corrector (PFC), are proposed. Simulation allowed to get the output characteristics and the dependences of the pulsation coefficients on the load variation of these converters. Also in this work comparative estimation of energy losses in PFC, transistor switches and the spectrums of consumption currents was made. References 9, table 1, figures 4.